Negosiasi dalam Reformasi Pemerintahan Daerah - HAMUDY, MOH. ILHAM A. (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The aim of the research is to analyze the process of negotiation or power sharing, between the stake holders which entirely affects the reform process, and the bureaucracy restructuring in order to support the reform process and public service in the Jembrana Regency, Bali - especially in health insurance policy. The research is descriptive and uses qualitative approach with the method of field research. The result of the research shows there are two factors that affect the local government reform in Jembrana Regency, i.e. the strong political commitment from the Regent, and the establishment of a stable centripetal democracy model.